A new species of the genus Clyzomedus Pascoe, 1865 from China (Coleoptera: Cerambycidae: Lamiinae: Mesosini) - Lin, Mei-Ying; Chen, Jiong; Yamasako, Junsuke (Zootaxa, 2023)
A new species Clyzomedus pani sp. nov. is described from Beijing, Shaanxi, Henan and Anhui, China. Quercus acutissima Carruth (Fagaceae) is the possible host plant. Images of habitus, external morphology and genitalia are provided. It is one of the currently discovered new species from Capital of China, since for the Biodiversity Survey and Assessment Project of Beijing.